IMPROVING SCIENCE LEARNING OUTCOMES THROUGH THE USE OF BIOTIC AND ABIOTIC COMPONENT BOARD MEDIA FOR GRADE III ELEMENTARY SCHOOL STUDENTS - Fatikhah Andan Sari; Najma Nurul Iza; Nadia Safira Putri; Mawardi; Ika Kartika (STMIK Indonesia Banda Aceh, 2026)
Learning Natural and Social Sciences (IPAS) in elementary schools aims to enable students to understand the surrounding environment through observing, grouping, and concluding activities. The reality in the field shows that student learning outcomes in the material of biotic and abiotic components are still low because learning is dominated by lecture methods so that students are less active and quickly bored. This study aims to improve student learning outcomes through the use of Biotic and Abiotic Component Board media. The study used the Classroom Action Research (CAR) method which was implemented in two cycles, with each cycle consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were six third-grade elementary school students. Data collection techniques used observation, documentation, and learning outcome tests. The results of the study showed an increase in learning outcomes at each stage. The average student score increased from 60 in the pre-cycle, to 70 in Cycle I, and increased again to 78 in Cycle II. The percentage of learning completion increased from 33% in the pre-cycle, to 66% in Cycle I, and reached 100% in Cycle II. The results of the study show that the use of Biotic and Abiotic Component Board media can improve the science learning outcomes of grade III elementary school students.